Experiences of reintegration and homelessness among mental health care users who have been treated and discharged from the Accra Psychiatric Hospital – A qualitative study - Williams, Beatrice Dwumfour (Stellenbosch : Stellenbosch University, 2020)
Thesis (MA)--Stellenbosch University, 2020.